Study on the utility of a statewide counselling programme for improving mortality outcomes of patients with Staphylococcus aureus bacteraemia in Thuringia (SUPPORT): a study protocol of a cluster-randomised crossover trial. Issue 4 (8th April 2017) - Weis, S; Hagel, S; Schmitz, R P H; Scherag, A; Brunkhorst, F M; Forstner, C; Löffler, B; Pletz, M W
Abstract : Introduction: Staphylococcus aureus bacteraemia (SAB) is a frequent infection with high mortality rates. It requires specific diagnostic and therapeutic management such as prolonged intravenous administration of antibiotics and aggressive search for and control of infectious sources. Underestimation of disease severity frequently results in delayed or inappropriate management of patients with SAB leading to increased mortality rates. According to observational studies, patient counselling by infectious disease consultants (IDC) improves survival and reduces the length of hospital stay as well as complication rates. In many countries, IDC are available only in some tertiary hospitals. In this trial, we aim to demonstrate that the outcome of patients with SAB in small and medium size hospitals that do not employ IDC can be improved by unsolicited ID phone counselling. The SUPPORT trial will be the first cluster-randomised controlled multicentre trial addressing this question. Methods and analysis: SUPPORT is a single-blinded, multicentre interventional, cluster-randomised, controlled crossover trial with a minimum of 15 centres that will include 250 patients with SAB who will receive unsolicited IDC counselling and 250 who will receive standard of care. Reporting of SAB will be conducted by an electronic real-time blood culture registry established for the German Federal state of Thuringia (ALERTSNet) or directly by participating centres in order to minimise time delay before counselling. Mortality, disease course and complications will be monitored for 90 days with 30-day all-cause mortality rates as the primary outcome. Generalised linear mixed modelling will be used to detect the difference between the intervention sequences. We expect improved outcome of patients with SAB after IDC. Ethics and dissemination: We obtained ethics approval from the Ethics committee of the Jena University Hospital and from the Ethics committee of the State Chamber of Physicians of Thuringia. Results will be published in a peer-reviewed journal and additionally disseminated through public media. Trial registration number: DRKS00010135.